Feminist Perspectives in the Poetry of Shah Abdul Latif Bhitai: A Narrative Literature Review - Shazia Shah; Sarala Thulasi Palpanadan; Ishfaque Ahmed Abbasi (Development in Language Studies, 2025)
Shah Abdul Latif Bhitai, one of the most revered Sufi poets of Sindh, presents a unique and progressive portrayal of women in his poetry. His exhibits highlight female autonomy, challenge patriarchal norms and emphasize female empowerment, agency, strength and self-determination. This literature review explores the feminist concepts embedded in Bhitai’s poetry, particularly through his depiction of legendary heroines such as Marvi, Sassui and Suhni, who embody strength, devotion and boldness against oppression. Using a narrative review approach, this research examines various research studies available in separate research databases that how Bhitai’s poetry aligns with feminist principles, advocating for gender equality and women’s empowerment within the cultural and mystical framework within Sindhi literature. The study discusses the research conducted on feminist vision of Bhitai. This study highlights the relevance of Bhitai’s poetry in shaping progressive narratives about women empowerment, Gender Equality and finding the research gap in connection with modern feminism therefore, this study will open the new doors of research on feminist concepts of Bhitai exist in his poetry.